Perceived Public Speaking Performance Predicts English Communication Confidence - Nisrina Mutia Oktavira; Dian Rahma Santoso (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Speaking competence is a central component of communicative proficiency, yet many learners experience anxiety and hesitation when addressing an audience in English. Specific Background: Public speaking tasks require not only linguistic mastery but also psychological readiness, particularly self-belief in one’s speaking ability. Knowledge Gap: While prior research has largely examined how anxiety constrains oral performance, limited attention has been given to how students’ own perceptions of their speaking performance relate to their confidence in English communication. Aims: This study investigates the correlation between students’ perceived public speaking performance and their confidence in communicating in English. Results: Using a quantitative correlational design with 33 Indonesian senior high school students, Spearman Rank-Order analysis revealed a statistically significant positive relationship (ρ = 0.609, p < 0.01). Students with higher perceived performance displayed greater fluency, spontaneity, and reduced anxiety, whereas less confident peers relied more on written scripts and showed hesitation. Novelty: The study foregrounds self-perception as a key psychological factor associated with communicative confidence, extending existing research beyond anxiety-centered explanations. Implications: Findings underscore the importance of structured speaking practice, constructive feedback, and psychologically supportive classrooms to foster both self-belief and communicative competence in English learning environments. Highlights: Positive self-evaluation aligns with smoother delivery, eye contact, and spontaneous responses. Learners with lower assurance depend heavily on prepared texts and exhibit frequent pauses. Supportive instructional settings and guided practice are essential for building communicative self-belief. Keywords: Public Speaking; Self-Perception; Communication Confidence; Speaking Performance; English Communication